AWARENESS OF ADVANCE DIRECTIVES AMONG HEALTHCARE PROFESSIONALS IN CRITICAL CARE UNITS OF A PRIVATE TERTIARY CARE HOSPITAL IN ISLAMABAD (Journal of Medical & Health Sciences Review, 2025)
Background: An advance directive is a verbal or written instruction that legally specifies a person’s health care preferences while they are not capable of making decisions for themselves. It is used to guide decisions on life sustaining treatment in the incident that they become incapacitated. Advance directives can take the form of a living will, a limitation of care document, a do not resuscitate order, or nomination of a health care proxy by a durable power of attorney.Purpose: The purpose of this study is to assess the awareness of the health care professionals (doctors and nurses) about advance directives, working in critical care units of tertiary care in a private hospital in Islamabad.Methods: A descriptive cross-sectional study was conducted to assess awareness regarding advance directives among 70 (40 nurses and 30 doctors). Descriptive analysis was done by using the software IBM SPSS (Statistical Package for Social Sciences) version 25.0. the study was approved by the ethics committee.Results: the study results showed that 51(72.90 %) respondents have the awareness of advance directives and 46 (65.70 %) respondents accepted that it is the responsibility of health care professionals to discuss Advance care directives with patients. Most of them were comfortable to discuss advance directives with patients and families. Many of them had formulated their own advance directives.Conclusion: Most of the participants agreed that advance directives are supportive in medical treatment decision-making.  Advance directives help decision making by healthcare professionals very easy. It reduces the chances of conflict within family members and with healthcare professionals.